Social and psychological guidelines of the victimological research of fraud victim - Попов, Костянтин Леонідович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
35617 people suffered from fraud (9% victims of all crimes) in 2014 in Ukraine. However, considering the high level of fraud latency, mentioned number hardly reflects the actual amount of people affected by fraud. Victimological problems were and still are an object of both national and foreign scientists’ researches. Often many works cover only general issues of victimology, and there is a very few amount of a detailed victimological research of fraud (among the newest is the thesis of S. I. Afanasenko "Victimological fraud prevention"). The article aims to identify a social and psychological orientations in victimological research of fraud. Clarification of socio-psychological characteristics of the individual victim of fraud involves coverage of the following aspects of the problem: socio-psychological acquired features of an individual (needs, interests, beliefs, habits, etc.); communication, and social and psychological interference of individuals in society in general and in certain social groups; features of the mechanism of motivation of the individual in a group and in joint activities of the members of different groups; features of the person’s reaction on the influence of his environment; patterns of group (mass) behavior. One of the important features that reflect the main socio-psychological and personality trait is a way of life, which is a combination of several different but related types of social activity. The article highlights the main features of social and psychological victimization’s environment of most victims of fraud. Fraud victim is investigated in terms of its economic (proprietary, property) subjectivity. Some additional guidelines are identified. In particular, social and psychological factors of criticality’s, discretion’s reduction of a person. However, as a fraud is a crime against property, based in many cases on the use of social (including interpersonal) relations and interactions that mediate property relations, a victimological analysis is required for the following questions: a) possible and acceptable for victims ways of acquisition, retention and disposal of property; b) the usual economic behavior of victims. Thus, with the provided scheme of social and psychological components and factors that contribute to victimization of fraud victims, you can get quite reliable socio-psychological portrait of a potential fraud victim, which will subsequently be used for the reduction or even neutralizing the risk to suffer from this crime.